Analysis of Goods Production Control Using The EOQ and ROP Method In Malaya Mart Bangkinang - Fifitri Ali; Ulvah Maysaroh (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
This study aims to compare the application of the EOQ method with the method used by the company in controlling the supply of merchandise inventory at Malaya Mart Bangkinang. This study analyzes the application of using the EOQ and ROP methods in 2020. From the research that has been done, it is known that the company's order frequency and total inventory costs have a large value and the company's policy does not have calculations for securing inventory and reorder points. Compared to using the EOQ and ROP methods, the frequency and total inventory costs have a small value and the EOQ and ROP methods calculate safety stock for merchandise inventory stock and re-inventory for merchandise inventory control.